2020
DOI: 10.37486/2675-1305.ec02036
|View full text |Cite
|
Sign up to set email alerts
|

New host plants records of Bactrocera carambolae Drew & Hancock, 1994 and Anastrepha spp. (Diptera: Tephritidae) in Brazil

Abstract: In this work we report five new host plants of Bactrocera carambolae Drew & Hancock, 1994 as well as new records of hosts of Anastrepha bahiensis Lima, 1937, Anastrepha fraterculus (Wiedemann, 1830), and Anastrepha striata Schiner, 1868 from samplings carried out in Mazagão county, Amapá-Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…However, so far this has only been recorded in areas already altered by human activity (Lemos et al 2014). Belo et al (2020) reported the species C. goetheanus as a host plant for B. carambolae, native to the Neotropical region and naturally occurring in peri-urban forests, revealing the adaptive capacity of this species. Iwahashi (1999Iwahashi ( , 2000 observed that B. carambolae evolved an aculeuslength adaptation capable of ovipositing on host plants native to Asian tropical forests.…”
Section: Bactrocera Carambolae Also Infestsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, so far this has only been recorded in areas already altered by human activity (Lemos et al 2014). Belo et al (2020) reported the species C. goetheanus as a host plant for B. carambolae, native to the Neotropical region and naturally occurring in peri-urban forests, revealing the adaptive capacity of this species. Iwahashi (1999Iwahashi ( , 2000 observed that B. carambolae evolved an aculeuslength adaptation capable of ovipositing on host plants native to Asian tropical forests.…”
Section: Bactrocera Carambolae Also Infestsmentioning
confidence: 99%
“…It occurs in specific areas of Amapá, Pará, and Roraima states (MAPA 2018). It is a polyphagous species, with 26 host plant species registered in Brazil, affecting fruits of high economic relevance, such as citrus and mangoes (Adaime et al 2016a; Belo et al 2020). This pest is considered as the main phytosanitary barrier to the export of fruits produced in Brazil (Silva et al 2004; Ferreira & Rangel 2015; Miranda & Adami 2015).…”
mentioning
confidence: 99%
“…This species is currently classified in Brazil as a quarantine pest and is under official control by the Ministry of Agriculture and Food Supply (Brasil, 2018). In addition to S. mombin, it has been recorded on 25 other host plants in Brazil, all of which occur in Amapá (Belo et al, 2020).…”
Section: Fruit Fly Infestation Of S Mombin In Amapámentioning
confidence: 99%
“…No Brasil, foi inicialmente detectada no município de Oiapoque, estado do Amapá, em 1996, e atualmente está distribuída em áreas restritas dos estados do Amapá, Pará e Roraima (Brasil, 2018). É uma espécie polífaga, com 26 espécies vegetais hospedeiras registradas no Brasil (Silva, et al, 2004;Adaime, et al, 2016;Belo, et al, 2020). Em decorrência das restrições quarentenárias impostas por países importadores, a praga é considerada a principal barreira fitossanitária para exportação de frutas produzidas no Brasil (Silva, et al, 2004;Godoy, et al, 2011a;Ferreira & Rangel, 2015;Miranda & Adami, 2015).…”
Section: Introductionunclassified